PENINGKATAN PENGETAHUAN IBU HAMIL MELALUI KELAS IBU HAMIL - Trisna Yuni Handayani; Desi Pramita Sari; Norma Jeepi Margiyanti; Suci Ridmadhanti; Reni Adelia Tarigan (Jurnal Inovasi dan Terapan Pengabdian Masyarakat, 2021)
Background The success of maternal health programs can be assessed through the main indicators of the Maternal Mortality Rate (MMR). The number of maternal deaths collected from the recording of family health programs at the Ministry of Health in 2020 was 4,627, an increase compared to 2019 of 4,221 deaths. Efforts to accelerate the decline in MMR can be done by ensuring that every mother is able to access quality health services. Pregnant Women Class is one way to reduce MMR. The Purpose of this activity is to increase knowledge of pregnant women about pregnancy. The method used is counseling, discussion, and demonstration. To determine the increase in knowledge, pretest and posttest were carried out. Results Of the 12 pregnant women before the activity was carried out 25% had good knowledge. After carrying out the activities of pregnant women with good knowledge category as much as 83%. Conclusion There was an increase in knowledge of pregnant women about pregnancy after the class of pregnant women was carried out.